Application and Analysis of Color Information using Tourist Attraction Image Processing for Souvenir Packaging Design - Ruxpaitoon, Kanakarn; Thiptarajan, Kasem; Lertrusdachakul, Thitiporn (JOURNAL OF INFORMATION SCIENCE AND TECHNOLOGY, 2020)
Packaging is the external appearance that creates the first impression and stimulates the needs of customers. The beautiful packaging with unique and consistent design particularly for souvenir of tourism will assist in product recognition and attract customers’ attention to create the story and increase the product value. As the color has greatly affected the psychological perception, this research therefore proposes the color analysis by image processing and applies to the design of souvenir packaging to communicate the meaning and convey the emotions of embedded image of the tourist attraction. The design concept and recommended colors are obtained from the analysis of representative colors, color image scale and place information. The representative colors are based on k-means clustering and the investigation from an art expert. The packaging designs of plai balm, plai oil and aroma oil; souvenirs of famous tourist attraction in Thailand, are used as the case studies in this research. The proposed design integrates the concept extracted from the image color analysis of overall exterior architecture and color tone of harmonious meaning. The evaluation results show that most respondents are more interested in buying the proposed packaging designs than the original ones. The results of design evaluation in perception of embedded feeling, desire of purchase and the suitability of color usage are all in high levels. The comments and suggestions from respondents are introduced to improve for more perfect packaging design.